1996
DOI: 10.1097/00007890-199604270-00026
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Drug Interaction Between Intravenous High-Dose Fluconazole and Cyclosporine or Tacrolimus in Bone Marrow Transplant Patients

Abstract: The purpose of this open-label, prospective study was to compare steady state concentrations and clearances of intravenously administered cyclosporine or tacrolimus with and without concomitant high-dose (400 mg/day) fluconazole in allogeneic BMT patients. Twenty-one patients were evaluable. The mean steady state cyclosporine and tacrolimus concentrations without fluconazole were 320.3 and 18.2 ng/ml and increased to 389.2 and 21.2 ng/ml, respectively, after the addition of fluconazole, corresponding to a 21% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
52
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(53 citation statements)
references
References 9 publications
0
52
1
Order By: Relevance
“…In a small prospective study in which fluconazole 400 mg daily was used in combination with tacrolimus in HSCT recipients, tacrolimus levels increased by 16% and tacrolimus clearance decreased by 16%. 17 A study in renal allograft recipients reported that tacrolimus patients with the CYP 3A5 3/*1 genotype (expressers) were less susceptible to fluconazole inhibition than CYP3A5*5 nonexpressers, suggesting that the magnitude of the azole-tacrolimus interaction could, in part, be explained by CYP3A expression. 18 In a prospective study in which tacrolimus was used in combination with itraconazole in HSCT recipients, tacrolimus levels were increased by a median 85%.…”
Section: Discussionmentioning
confidence: 99%
“…In a small prospective study in which fluconazole 400 mg daily was used in combination with tacrolimus in HSCT recipients, tacrolimus levels increased by 16% and tacrolimus clearance decreased by 16%. 17 A study in renal allograft recipients reported that tacrolimus patients with the CYP 3A5 3/*1 genotype (expressers) were less susceptible to fluconazole inhibition than CYP3A5*5 nonexpressers, suggesting that the magnitude of the azole-tacrolimus interaction could, in part, be explained by CYP3A expression. 18 In a prospective study in which tacrolimus was used in combination with itraconazole in HSCT recipients, tacrolimus levels were increased by a median 85%.…”
Section: Discussionmentioning
confidence: 99%
“…In two reviews, 3,4) there was an impact of interaction between triazole antifungal agents and calcineurin inhibitors when both medicines were orally administered. In our result (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][7][8][9][10][11][12][13][14][15][16] Calcineurin inhibitors are routinely administered as prophylaxis for graft versus host disease (GVHD) in patients receiving allogeneic HSCT (allo-HSCT). [17][18][19] Triazole antifungal agents are metabolized by the cytochrome P450 (CYP) enzyme system, CYP2C9, CYP2C19, and CYP3A4 isozymes, 8,10) whereas the calcineurin inhibitors are primarily metabolized by CYP3A4.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Drug interactions with tacrolimus that are known to occur or for which a strong possibility for interaction exists are listed in Table 3. Agents known to induce or inhibit the P450 enzyme system should be administered with caution to patients receiving tacrol- Table 3 Potential drug interactions with tacrolimus 27,30,115,116,[120][121][122][123][124][125][126][127][128][129] imus, and close therapeutic drug monitoring should be performed. Pharmacokinetic studies in BMT patients who received tacrolimus alone or in combination with methylprednisolone or methotrexate showed no difference in clearance of tacrolimus.…”
Section: Drug Interactionsmentioning
confidence: 99%